Thirty Years of Fiscal Decentralization Research: a Bibliometric Analysis - Muhammad Aliyuddin (JFBA: Journal of Financial and Behavioural Accounting, 2023)
Fiscal decentralization has become a trend in countries around the world over the past few decades. Therefore, it is necessary to investigate the impact of fiscal decentralization on economic, social, and political aspects. The rapid development of publications on fiscal decentralization makes it difficult to synthesise a complete, streamlined, and relevant body of knowledge. Therefore, this study aims to find out about the latest developments of related research topics in fiscal decentralization. The research method used in this study is bibliometric analysis using the Voswiewer application. The bibliometric techniques used in this research are performance analysis and science mapping. The data source in this study comes from Dimensions.ai.  Based on the results of the analysis in this study, it can be seen that research related to fiscal decentralization is mostly carried out in China. The relationship between fiscal decentralization and environmental as well as energy issues is the latest trend in the field of fiscal decentralization research.